1981
DOI: 10.1093/jn/111.11.1928
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality and Digestibility of Sorghum in Preschool Children: Balance Studies and Plasma Free Amino Acids

Abstract: The protein quality and digestibility of two high lysine (2.9-3.0 g/100 g protein) and tow conventional varieties (lysine content 2.1-2.2 g/100 g protein) of whole grain sorghum milled as flour were assessed through balance studies in 13 children 6-30 months of age. Sorghum protein provided 6.4 or 8.0% of dietary energy. Control diets contained 64% kcal protein as casein. Children consumed 100-150 kcal/kg body weight/day. Sorghum consumption was associated with weight loss or poor weight gain. We found no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 18 publications
2
64
0
1
Order By: Relevance
“…Although numerous studies have been conducted with human subjects (Table 3 (19,29,35,58,67, ), the majority have addressed micronutrient metabolism (such as interactions between leucine, molybdenum, and niacin), (129) iron absorption from cereals, (35) dietary fiber effects, (140) protein digestibility (144) and oral rehydration therapies. (148) This review therefore summarizes the experimental evidence that suggests protective health effects of sorghum consumption, targeting studies that investigate effects on energy balance, glycemic control, lipids, oxidative stress and cell-mediated responses.…”
Section: Experimental Research On Sorghum Consumptionmentioning
confidence: 99%
“…Although numerous studies have been conducted with human subjects (Table 3 (19,29,35,58,67, ), the majority have addressed micronutrient metabolism (such as interactions between leucine, molybdenum, and niacin), (129) iron absorption from cereals, (35) dietary fiber effects, (140) protein digestibility (144) and oral rehydration therapies. (148) This review therefore summarizes the experimental evidence that suggests protective health effects of sorghum consumption, targeting studies that investigate effects on energy balance, glycemic control, lipids, oxidative stress and cell-mediated responses.…”
Section: Experimental Research On Sorghum Consumptionmentioning
confidence: 99%
“…The nutritional quality of sorghum protein is of concern because, besides being low in the essential amino acid Lys, it has lower digestibility than protein of other cereal grains. Human studies in Peru (1) showed apparent protein digestibility of cooked sorghum to be only 46%, whereas values of 81, 73, and 66% were reported for cooked wheat, maize, and rice, respectively.…”
mentioning
confidence: 95%
“…Other unpublished data from our group showed that environmental conditions during the growing season also influence sorghum protein digestibility. In addition, processing methods affect digestibility, such as whether sorghum is boiled to a porridge, fermented, decorticated and extruded, or germinated (1,(4)(5)(6)(7)(8). Simple cooking of sorghum flour has an uncommon and detrimental effect of decreasing protein digestibility as demonstrated by in vitro (4,5) and in vivo (9,10) studies.…”
mentioning
confidence: 99%
“…However, like other cereals, sorghum has poor protein quality because of lack of essential amino acids such as lysine and tryptophan [1][2][3][4] . Compounding this problem, sorghum proteins have very poor digestibility.…”
mentioning
confidence: 99%
“…Compounding this problem, sorghum proteins have very poor digestibility. These properties result in severe malnutrition when sorghum is consumed as the primary protein source 3 . The predominant seed proteins in sorghum are alcoholsoluble prolamins called kafirins.…”
mentioning
confidence: 99%